Diseño y estandarización de la planta piloto de tratamiento de agua tipo compacta, en la Universidad de América. (2022)
In the degree project "design and standardization of the compact type water treatment pilot plant, at the University of America". An analysis is made of the substances that are planned to be used in the CEPIIS (Center for processes and innovation for sustainable industry), which will have to be treated in the compact treatment plant; These substances are grouped by chemical nature, which allows generating a possible treatment. By having the evaluation of the substances, an investigative process of the advances in technology is carried out and how they can be incorporated into the proposal to be made.